Correlation between obstructive sleep apnea and hypoperfusion in patients with acute cerebral infarction - Zhou, Yi; Jin, Xiaomei; Liu, Xiaorong; Tang, Jiafan; Song, Liyan; Zhu, Yu; Zhai, Wanqing; Wang, Xianhui (Frontiers in Neurology, 2024)
Purpose To explore the relationship between obstructive sleep apnea (OSA) and hypoperfusion during ultra-early acute cerebral infarction. Patients and methods Data were retrospectively collected from patients admitted to our hospital with acute cerebral infarction between January 2020 and January 2022, who underwent comprehensive whole-brain computed tomography perfusion imaging and angiography examinations within 6 h of onset. The F-stroke software automatically assessed and obtained relevant data (Tmax). The patients underwent an initial screening for sleep apnea. Based on their Apnea-Hypopnea Index (AHI), patients were categorized into an AHI ≤15 (n = 22) or AHI >15 (n = 25) group. The pairwise difference of the time-to-maximum of the residue function (Tmax) > 6 s volume was compared, and the correlation between AHI, mean pulse oxygen saturation (SpO2), oxygen desaturation index (ODI), percentage of time with oxygen saturation < 90% (T90%), and the Tmax >6 s volume was analyzed. Results The Tmax >6 s volume in the AHI > 15 group was significantly larger than that in the AHI ≤ 15 group [109 (62–157) vs. 59 (21–106) mL, p = 0.013]. Spearman’s correlation analysis revealed Tmax >6 s volume was significantly correlated with AHI, mean SpO2, ODI, and T90% in the AHI > 15 group, however, no significant correlations were observed in the AHI ≤ 15 group. Controlling for the site of occlusion and Multiphase CT angiography (mCTA) score, AHI (β = 0.919, p < 0.001), mean SpO2 (β = −0.460, p = 0.031), ODI (β = 0.467, p = 0.032), and T90% (β =0.478, p = 0.026) remained associated with early hypoperfusion in the AHI > 15 group. Conclusion In patients with acute cerebral infarction and AHI > 15, AHI, mean SpO2, ODI and T90% were associated with early hypoperfusion. However, no such relationship exists among patients with AHI ≤ 15.